Utilization of safe drinking water and sanitary facilities in slum households of Siliguri, West Bengal - Ditipriya Bhar; Sharmistha Bhattacherjee; Abhijit Mukherjee; Tapas Kumar Sarkar; Samir Dasgupta (Wolters Kluwer Medknow Publications, 2017)
Background: With the rapid expansion of urban population, provision of safe water and basic sanitation is becoming a challenge; especially in slums. This is adversely affecting the health of the people living in such areas. Objectives: The study was conducted to measure the proportion of households using improved drinking water and sanitation facilities and to determine the association between diarrhea in under-five children with water and sanitation facilities. Methods: A community-based, cross-sectional study was conducted among 796 slum households in Siliguri from January to March 2016 by interviewing one member from each household using a predesigned and pretested questionnaire based on the WHO/UNICEF Joint Monitoring Program Core questions on drinking water and sanitation for household surveys. Results: A majority 733 (92.1%) of slum households used an improved drinking water source; 565 (71%) used public tap. About two-thirds (65.7%) household used improved sanitation facilities. About 15.8% households had reported diarrheal events in children in the previous month. Unimproved drinking water sources (AOR = 4.13; 1.91, 8.96), houses without piped water supply (AOR = 4.43; 1.31, 15.00), and latrines located outside houses (AOR = 3.61; 1.44, 9.07) were significantly associated with the diarrheal events in children. Conclusion: The utilization of improved drinking water source was high but piped water connection and improved sanitary toilet used was low. Association between diarrheal events and type of drinking water sources and place of sanitation might suggest fecal contamination of water sources. Awareness generation through family-centered educational programs could improve the situation.